Extended Solution Gate OFET‐Based Biosensor for Label‐Free Glial Fibrillary Acidic Protein Detection with Polyethylene Glycol‐Containing Bioreceptor Layer. (23rd March 2017) - Song, Jian; Dailey, Jennifer; Li, Hui; Jang, Hyun‐June; Zhang, Pengfei; Wang, Jeff Tza‐Huei; Everett, Allen D.; Katz, Howard E.
Abstract : A novel organic field effect transistor (OFET)‐based biosensor is described for label‐free glial fibrillary acidic protein detection. This study reports the first use of an extended solution gate structure where the sensing area and the organic semiconductor are separated, and a reference electrode is not needed. Different molecular weight polyethylene glycols (PEGs) are mixed into the bioreceptor layer to help extend the Debye screening length. The drain current change is significantly increased with the help of higher molecular weight PEGs, as they are known to reduce the dielectric constant. This study also investigates the sensing performance under different gate voltage ( V g ). The sensitivity increases after the V g is decreased from −5 to −2 V because the lower V g is much closer to the OFET threshold voltage and the influence of attached negatively charged proteins becomes more apparent. Finally, the selectivity experiments toward different interferents are performed. The stability and selectivity are promising for clinical applications. Abstract : A novel organic field effect transistor‐based biosensor is described for label‐free glial fibrillary acidic protein detection. Different molecular weight polyethylene glycols are mixed into the bioreceptor layer to help extend the Debye screening length. The sensitivity increases while V g decreases since lower V g is much closer to the OFET threshold voltage and the influence of attached proteins becomes more apparent.